MO773THE VASCULAR REALITY BEHIND ULTRASOUND VASCULAR MAPPING: WHICH FACTORS PREDICT THE BEST CANDIDATES FOR RADIOCEPHALIC ARTERIOVENOUS FISTULA?. (29th May 2021) - Barata, Rui; Pereira, Tiago; Marques, Joana; Bigotte Vieira, Miguel; Nolasco, Fernando
Abstract: Background and Aims: Vascular accesses (VA) are key components for efficient hemodialysis. Arteriovenous fistulas (AVF) are recommended over arteriovenous graft (AVG), but deciding the type and location of a VA is challenging. Preoperative vascular mapping before surgical creation of VA, especially trough ultrasound (US), is helpful in this decision, contributing to improve AVF e AVG outcomes. Our study aims to identify patient factors associated with appropriate arterial US parameters that predict feasibility for radiocephalic fistula creation. Method: We analyzed a cohort of chronic kidney disease patients who underwent US vascular mapping for preoperative planning of dialysis access from 2019 to 2020, in a tertiary referral center. Patients were characterized based on its demographical characteristics, and the presence of diabetes, hypertension, obesity, and smoking. Arterial indicators were analyzed by ultrasound techniques in both upper arms, including radial, ulnar and brachial arteries. Those indicators included arterial diameter, calcification, doppler wave form, and pulse wave velocity. Continuous variables were recorded as means (±SD) for normally distributed data and as medians (interquartile ranges) for nonnormally distributed data. Comparisons were made using t tests or Wilcoxon rank sum tests as appropriate. Categorical variables were examined by frequency distribution and recorded as proportions. Comparisons were made using the x2 test. Unadjusted and adjusted multivariate logistic regression models were fitted to identify predictors for a good candidate for radiocephalic arteriovenous fistula. Results: A total of 252 patients were included. The mean age was 65±16 years, 144 (57%) were male, 211 (84%) where white, 40 (16%) were black, and 1 (0.4%) was asian. Most had arterial hypertension (205, 81%), 98 (39%) had diabetes mellitus, 89 (35%) were smokers, and 72 (29%) were obese. The majority of patients were attending for the first VA (186; 74%). Most patients were considered appropriate candidates for arteriovenous fistula creation (207, 82%), whereas 45 (18%) were assigned to PTFE graft. Obesity and male sex were found to be predictors for being a good candidate for radiocephalic arteriovenous fistula in a multivariate logistic regression model adjusted for age, hypertension, and diabetes (OR 3.21, CI 95% 1.63-6.32, p-value 0.001 and OR 2.09, CI 95% 1.07-4.08, p-value 0.031, respectively). Figure 1 presents the arterial indicators analyzed during ultrasound mapping, including both upper limbs. Conclusion: Our results show that obesity and male sex are predictors for radiocephalic arteriovenous fistula creation. While female sex has long been known to be a risk factor for VA failure, possibly because of worse arterial indicators, an association between obesity and higher probability of distal AVF creation has not been established yet. Comparison between arterial indicators in obese and nonobese patients shows that obese patients generally have better arterial indicators, especially higher pulse wave velocities, and less arterial calcification. Given that some studies show an association between obesity and shorter fistula survival (due to higher secondary failure rate), our results may come as. A possible explanation for this difference is that obesity may exert a physical protective effect of the forearm vascular bed against iatrogenic damage (blood sampling and vessel cannulation). Besides that, factors other than vascular indicators may contribute to ulterior VA failure, like the proinflammatory state in obese patients and its consequent myointimal hyperplasia. However, our conclusions are based on preoperative findings, and not on VA outcomes, especially its patency and complications. Moreover, which further help to determine the better location for a VA creation, were not evaluated in this study.